Oral Administration of Bacillus toyonensis Strain SAU-20 Improves Insulin Resistance and Ameliorates Hepatic Steatosis in Type 2 Diabetic Mice - Ren, Zhihua; Okyere, Samuel Kumi; Xie, Lei; Wen, Juan; Wang, Jiayi; Chen, Zhengli; Ni, Xueqin; Deng, Junliang; Hu, Yanchun (Frontiers in Immunology, 2022)
In this study, the ameliorative effects of Bacillus toyonensis-SAU-20 (B. toyo SAU-20), a new probiotic strain isolated and identified by our laboratory from Ageratina adenophora, on the development of insulin resistance and hepatic steatosis in type 2 diabetic (T2DM) mice was investigated. Thirty Specific-pathogen free Kunming (SPFKM) mice were randomly allocated to three groups: control, high fat diet/streptozotocin (HFD/STZ), and HFD/STZ+B. toyo SAU-20 groups with oral administration of B. toyo SAU-20 for 35 days. Biochemistry parameters, glucose tolerance, and insulin resistance were measured in the blood whereas histological analysis, inflammatory cytokines and lipogenic genes in the liver tissues. The results showed that, the levels of serum glucose, lipid profile, mRNA expression of lipogenic related genes and pro-inflammatory cytokines were significantly increased in T2DM mice. However, after B. toyo SAU-20 administration, the elevation of these parameters was significantly suppressed (P<0.05). In addition, the feeding of B. toyo SAU-20 significantly improved the morphological changes of the liver with significant alleviation of dyslipidemia, oxidative stress status and inflammation (P<0.05) indicating the ameliorating effect of B. toyo SAU-20 in hepatic steatosis in T2DM. Therefore, we concluded that, B. toyo SAU-20 alleviated insulin resistance and hepatic steatosis by improving the lipid profiles, antioxidant status and downregulating lipogenic genes as well as pro-inflammation cytokines expression.